TUG-Defined Mobility Impairment and Physical Performance in Adults with Type 2 Diabetes Mellitus - Madawi Aljawaee; Neah Albasha; Rakan I. Nazer; Ali M. Albarrati (Journal of Clinical Medicine, 2026)
Background/Objectives: Type 2 diabetes mellitus (T2DM) is increasingly recognised as a risk factor for physical frailty, driven by sarcopenia, microvascular disease, and chronic hyperglycaemia. Simple, low-cost performance tests may offer a practical means of identifying frailty risk in this population, but data combining several such measures in T2DM remain limited. This study aimed to characterise physical performance and quantify the proportion of adults with T2DM meeting thresholds for low physical performance. Methods: In this cross-sectional study, physical performance was assessed in adults with T2DM using the Timed Up and Go (TUG) test, handgrip strength (HGS), and the six-minute walk distance (6MWD). TUG cutoffs of 8 and 10 s were applied as exploratory external reference thresholds, consistent with cutoffs previously applied in chronic disease and older-adult populations. Results: Participants had a mean age of 55.6 ± 4.8 years; 42 (64.6%) were male, and mean BMI was 29.6 ± 4.4 kg/m2. Mean TUG time was 9.30 ± 3.02 s, right and left HGS were 30.8 ± 10.1 kg and 28.0 ± 9.3 kg, and mean 6MWD was 401.2 ± 96.3 m. Forty-four participants (67.7%; 95% CI 55.6–77.8) exceeded the 8 s threshold, and 16 (24.6%; 95% CI 15.8–36.3) exceeded 10 s. TUG correlated strongly and inversely with 6MWD (r = −0.75, 95% CI −0.84 to −0.61; p < 0.001). This remained unchanged after adjustment for age, sex, and BMI (r = −0.76) and held within men (r = −0.79) and women (r = −0.78) separately. Handgrip strength correlated with 6MWD (right r = 0.40; left r = 0.39; both p ≤ 0.001) and attenuated to non-significance after adjustment for sex (r = 0.22, p = 0.076) and for age, sex, and BMI (r = 0.18, p = 0.16). In multivariable regression, TUG was independently associated with 6MWD (−21.4 m per second, p < 0.001), whereas handgrip strength was not (p = 0.064). Conclusions: A substantial proportion of adults with T2DM in this cohort displayed low-physical-performance profiles. Simple performance batteries combining TUG, handgrip strength, and 6MWD warrant further study as a potential means of identifying patients with T2DM who could benefit from targeted rehabilitation.